Philosophy in engineering education - Nataliya V. Popkova (Высшее образование в России)
In the article the position of philosophy as the subject intended for obligatory studying by the future technical experts is considered. Merits and demerits of a philosophical discourse for dominating technical rationality are shown. The leading role of philosophy in construction of a new, not-technogenic and more humane society is defined.